For simplifying a complex rational expression we make use of copmlex conjugate( multiply and divide by the complex conjugate of the denominator).

e.g. In simplifying (1-i)/(1+i).

The complex conjugate of the denominator (1+i) is (1-i)

so (1-i)*(1-i)/(1+i)*(1-i)=(1-i)^2/(1-i^2)

=(1-2i+i^2)/(1-i^2)

= (-2i)/2 as i^2=-1

= -i.

`1/(a+ib)=(a-ib)/{(a+ib).(a-ib)}`

` = (a-ib)/(a^2+b^2) `

...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

For simplifying a complex rational expression we make use of copmlex conjugate( multiply and divide by the complex conjugate of the denominator).

e.g. In simplifying (1-i)/(1+i).

The complex conjugate of the denominator (1+i) is (1-i)

so (1-i)*(1-i)/(1+i)*(1-i)=(1-i)^2/(1-i^2)

=(1-2i+i^2)/(1-i^2)

= (-2i)/2 as i^2=-1

= -i.

`1/(a+ib)=(a-ib)/{(a+ib).(a-ib)}`

` = (a-ib)/(a^2+b^2) `

`=a/(a^2+b^2)-i b/(a^2+b^2)`

`` means we multiply and devide by complex conjugate of the denomonator and simplify.